PEMBERDAYAAN KELOMPOK TANI MELALUI PELATIHAN PENGENDALIAN HAMA DAN PENYAKIT TANAMAN KAKAO DI KANAGARIAN CAMPAGO KABUPATEN PADANG PARIAMAN - Ujang Khairul; Trizelia Trizelia; Reflin Reflin (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2018)
Training on methods of pests and diseases management in cocoa plants has been conducted in the Nagari Campago, Kecamatan V Koto Kampung Padang Pariaman. The aims of this activity was to empower farmer groups through increasing the knowledge of cocoa farmers about cultivation and pests and diseases management attacked of cocoa plant, this activity consists of socialization, counseling and field practice. Evaluations carried out before and after training related to farmers' knowledge about cultivation and pests and diseases in cocoa. The results of the activity show that: (a) the level of pests and diseases in cocoa plantations in this area is quite high (55% dan 65%), (b) farmers have not good cultivated on cocoa, (c) farmers do not understand abaut pests and diseases that attack their cocoa and do not understand the methods for controlling pests and diseases. This activity has increased farmers' knowledge about the cultivation and management of pests and diseases in cocoa plants.